MEASURING SERVICE-LEARNING PROGRAMS BY UNIVERSITIES ON BOARDING SCHOOLS (International Conference on Social and Islamic Studies, 2021)
Islamic boarding schools or pesantren have to adapt to face the various problems that arise in the global era. Each has many resources that have the potential to be developed. The role of universities around the pesantren area can promote the pesantren as a qualified institution and provide quality human resources. Service-learning activities are one type of creative work that universities can do that engages with the community. This literature study article measures the position of service-learning programs at Islamic boarding schools conducted by universities. The result shows that performing service-learning activities involves several stages. The stages are planning as part of pre-implementation, implementation of service-learning activities and reflection as the implementation stage, and assessment, recognition, and celebration as part of the post-implementation stage. The position of the service-learning program in Islamic boarding schools carried out by universities is feasible because service-learning can comprehensively solve problems in the pesantren environment.